A Study On Soil Bearing Capacity Strengthening Using Soil Cement On Jagebob Road With Unconfined Compression Test - Erdawaty; Ritnawati; Fitriana, Tati; Adriati, Yolly; Tondok, Sapri Sampe (UIR PRESS, 2025)
This study investigates the improvement of soil bearing capacity through the application of soil–cement stabilization on Jagebob Road using the Unconfined Compression Test (UCT). The research aims to evaluate how curing duration affects the compressive strength development of soil cement mixtures. Laboratory experiments were conducted on cohesive soil samples with curing periods of 0, 3, and 7 days to observe the changes in both physical and mechanical properties. The results show that at 0 days of curing, the compressive strength remained low (0.103–0.114 kg/cm²) due to incomplete hydration. After 3 days, a significant increase in strength was observed, reaching up to 0.295–0.305 kg/cm², indicating the beginning of cement hydration and improved particle bonding. At 7 days, the soil achieved even higher compressive strength as the hydration process produced more calcium silicate hydrate (C-S-H) and calcium hydroxide (Ca(OH)₂), which enhanced the density and bonding of the soil matrix. These findings confirm that the curing period plays a crucial role in strengthening soil cement. Therefore, a curing duration of at least seven days is recommended to achieve optimal mechanical performance and ensure improved bearing capacity of stabilized soils for road infrastructure such as Jagebob Road.